The impact of pre‐round meetings on quality of care: A qualitative study - Lars Kyte; Irene Sjursen; Ole T. Kleiven (Wiley, 2020)
Abstract Aim This study's aim was to improve our understanding of the impact of pre‐round meetings before ward rounds on hospital wards. Design Qualitative study. Method Focus group interviews were conducted with nurses and doctors. Results Participants reported that pre‐round meetings provide opportunities for interdisciplinary cooperation and have a positive impact on the quality of treatment and care. These meetings offer a forum for health professionals to develop a shared understanding and to convey congruent information to the patient. However, there may be reasons for omitting the pre‐round meetings before ward rounds on wards with acute admissions and high patient turnover. Continuity of those attending the meetings and attendance by consultants are needed for timely decision‐making and hence, successful pre‐round meetings. If health trusts establish systems promoting successful pre‐round meetings, the quality of treatment received by patients has potential for improvement.